Characterizing the pore structure in the Silurian and Permian shales of the Sichuan Basin, China. (March 2015) - Cao, Taotao; Song, Zhiguang; Wang, Sibo; Cao, Xinxing; Li, Yan; Xia, Jia
Abstract: Nitrogen sorption and mercury intrusion methods were applied to characterize the pore structure of the Lower Silurian shales of the Long-ma-xi Formation and Upper Permian shales of the Da-long Formation in the Sichuan Basin. The results indicate that the specific surface areas and porosities of the Silurian shales are in the range of 17.83–29.49 m 2 /g and 3.65–18.26%, respectively. The Silurian shales show a bimodal pore-size distribution, and consist of both micropores and nanopores, ranging from 30 to 60 μm and 1.7–20 nm, respectively. A strong positive linear correlation between the surface areas and total organic carbon content (TOC) suggests that the organic matter contributes mostly to the amount of specific surface area of the Silurian shales, whereas the contribution of clay minerals appears to be negligible. The organic matter also accounts for 50–70% of the porosity in the Silurian shales. Soluble organic matter in the form of bitumen, however has a negative impact on the surface area and porosity of the Silurian shales and reduce the amount of surface area and porosity in these shales. For the Permian shales, their surface area and porosity are lower than those of the Silurian shales, and are in the ranges of 2.20–3.52 m 2 /g and of 1.30–4.15%, respectively. The pore-size distribution of the Permian shales shows a unimodal pattern of micropores in a size range of 30–60 μm. Their TOC and clay mineral contents display poor correlation with the surface areas and suggest that both the organic matter and clay minerals have very low surface areas. A clear negative correlation between the porosity and TOC in the Permian shales indicates that organic matter contributes little or insignificantly to the porosity due to poorly developed organic pores in kerogen because the Permian shales are much lower in thermal maturity than the Silurian shales. Furthermore, there is a consistent negative linear correlations between the bitumen content and the porosity for both the Permian shales and Silurian shales and indicate that the bitumen may significantly reduce the porosity of the shales by occupying the pore spaces in the mineral and organic matrix. Finally, it is clear that the Lower Silurian shales have a greater shale gas potential than the Upper Permian shales do based on their surface area and porosity. Highlights: Permian shales display low surface area and porosity compared to Silurian shales. TOC content is the controlling factor of pore structure in Silurian shales. The maturity and organic matter type control the development of organic pores. Bitumen shows negative impact on the surface area and porosity of the shales.